Shallow-water marine molluscs of the Azores : biogeographical relationchips. - Ávila, Sérgio P. (2011)
Shallow-water marine molluscs of the Azores were surveyed from supralittoral to a depth of 45 m which yielded an up-to-date database. The resulting list of 231 confirmed taxa of the Azores was then compared with similar lists from Scandinavia, Belgium, British Isles. Gulf of Biscay to Galiza. Portugal, Western Mediterranean. Morocco and Mauritania, Madeira, Porto Santo, Desertas and Selvagens, Canary Islands. Cape Verde, Ascension Island? Saint Helena, and the Caribbean. A total of 18 species and 1 subspecies (Tricolia pullus azorica) are considered to be endemic to the Azores. There arc 20 new records to the Azores: Metaxia abrupta(Watson, 1880), Monophorus erythrosoma(Bouchet & Guillemot, 1978), Melanella sp., Lamellaria latens (0. F. Muller, 1776), Ranella olearia (Linnaeus, 1758), Ocinebrina edwardsi (Payraudeau, 1826), Fusinus sp., Nassarius corniculus (Olivi, 1792), Crassopleura incrassata (Dujardin, 1837). Heliacus architae (O.G. Costa, 1867), Cima cf. minima (Jeffreys, 1858). Odostomia conoidea (Brocchi, 1814), Ondina diaphana (Jeffreys, 1848), Chromodoris khroni (Verany, 1846), Chlamys flexuosa Poli. 1795, Loripes lacteus (Linnaeus, 1758). Bornia sp., Parvicardium exiguum (Gmelin, 1791), Gastrana fragilis (Linnaeus. 1758) and Praphia aurea (Gmclin, 1791). It was possible to infer the life history of only 72 species out of the 231. Of these, 38 have a free-swimming stage and 34 have a non-planktotrophic type of development (cither lecithotrotrophic or direct development). Thirteen endemic species were found with a non-planktotrophic type of development, all belonging to the Rissoidae. The Mediterranean, Madeira archipelago and Portugal mainland, are the regions which share a higher number of species with the Azores, whereas Saint Helena and Ascension Island share only a small number of species with the Azores. Some comments are made regarding the influence of the Gulf Current on the composition of the marine malacofauna of the Azores, as well on the possible routes of colonization of the Azorean islands by marine molluscs.